The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/jms.767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal cationization on the tandem mass spectra of glycosyl dithioacetals

Abstract: The effect of metal cationization on the tandem mass spectra of glycosyl dithioacetals of glucose, mannose, galactose, rhamnose, arabinose and xylose was studied by electrospray ionization mass spectrometry under ammonium and metal (Li, Na, Ag and Cu) ion cationization conditions. The ammonium-cationized glycosyl dithioacetals fragment by loss of ammonia followed by either two molecules of EtSH or one molecule of EtSH and one molecule of H2O. Lithium cationization leads to additional eliminations such as EtSEt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The m/z value of the ions corresponding to C 2 H 4 O 2 elimination is partly shifted to m/z 223 in 1B , suggesting that multiple mechanisms operate for this elimination. This is consistent with involvement of cyclization in EtSH elimination, as proposed by us previously 24…”
Section: [M+xcl]+supporting
confidence: 93%
See 1 more Smart Citation
“…The m/z value of the ions corresponding to C 2 H 4 O 2 elimination is partly shifted to m/z 223 in 1B , suggesting that multiple mechanisms operate for this elimination. This is consistent with involvement of cyclization in EtSH elimination, as proposed by us previously 24…”
Section: [M+xcl]+supporting
confidence: 93%
“…Metal cationization alters the stability of the resulting products and thus changes the dissociation pathways 23. As a continuation of our earlier study on the effect of metal ions such as Li + , Na + , Ag + and Cu + on the MS/MS spectra of glycosyl dithioacetals,24 we have examined the MS/MS spectra of glycosyl dithioacetals 1 – 6 complexed to ligated metal ions (CoCl + , MnCl + and ZnCl + ) with a view to studying the effect of different metal ions on fragmentation, and to explore the possibility of distinguishing the stereoisomers. …”
mentioning
confidence: 65%
“…8,13 Knowledge of the fragmentation mechanisms of lactones and the behaviour of these compounds under ESI conditions can be extended to larger and more complex natural products that contain the a,b-unsaturated g-lactone moiety in their structure. Little is known about the gas-phase behaviour of a,b-unsaturated g-lactones linked or fused to sugars, [14][15][16][17] and to the best of our knowledge, there have been few studies of the fragmentation behaviour of monosaccharides. 18 We decided, therefore, to perform a detailed study using ESI-MS and ESI-MS/MS on five a,b-unsaturated g-lactones (butenolides) fused to a furanose ring, recently synthesized compounds which may possess interesting biological properties.…”
mentioning
confidence: 99%
“…114 Metal cationization involving alkali and transition metal ions and silver ion under ESI has been studied with acyclic sugar derivatives, cyclodextrins, glycosyl dithioacetals, aldohexoses, ketohexoses, glycosyl sulfides, sulfoxides and sulfones and the fragmentations under CID have been rationalised. [115][116][117][118][119] CID of ammonium adducts of monosaccharides has differentiated diastereoisomers. In addition, it was found that the ion abundances from CID of oxocarbenium ions generated from aldohexoses and ketohexoses under ESI conditions were different for diastereoisomers and the ratios of the abundances of two of the major ions m/z 85 and m/z 91 were different in the aldohexoses and the ketohexoses.…”
Section: Introductionmentioning
confidence: 99%